PATH-39. DNA MISMATCH REPAIR ENZYME IMMUNOHISTOCHEMISTRY IS A RAPID, EFFECTIVE SCREENING TEST FOR HYPERMUTATED GLIOMAS. (11th November 2019) - McCord, Matthew; Steffens, Alicia; Kam, Kwok-Ling; Javier, Rodrigo; McCortney, Kathleen; Horbinski, Craig
Abstract: BACKGROUND: While gliomas with hypermutated DNA are resistant to alkylating agents like temozolomide, they may be especially responsive to immunotherapy, since they express abundant neoantigens on their cell surfaces. Screening for hypermutated gliomas is currently being done through next-generation sequencing (NGS) panels that cover large portions of tumor DNA, although this is costly and access to such testing is not universal. Since hypermutated gliomas typically contain inactivating mutations in one of the main DNA mismatch repair (MMR) proteins, and cancers with an MMR mutation usually show loss of normal MMR protein, we sought to determine the feasibility of rapidly screening for hypermutated gliomas with an MMR immunohistochemistry (IHC) panel that is already in widespread use for colorectal adenocarcinomas. METHODS: Tumor mutation burden (TMB) was determined via NGS for 101 gliomas, including 64 GBMs, 24 grade II-III astrocytomas, 9 grade II-III oligodendrogliomas, and 4 grade I gliomas. IHC for MSH2, MSH6, MLH1, and PMS2 was performed and analyzed on all gliomas while blinded to mutation profile and TMB. RESULTS: Seven of 101 gliomas (7%) showed loss of an MMR protein by IHC. All 7 had matching MMR gene mutations and were hypermutated (100%), defined as TMB >20 per megabase of DNA. Of the remaining 94 with intact MMR IHC, only one was hypermutated. That case had an inactivating splice region mutation in another gene involved in DNA repair, ATM, although ATM is not part of the IHC panel originally developed for colorectal cancer. Overall sensitivity and specificity of the current MMR IHC panel for hypermutated gliomas was therefore 88% and 100%, respectively. CONCLUSION: The colorectal MMR IHC panel, available in virtually all clinical IHC labs, is also a good screening test for hypermutated gliomas. Expansion of the panel to include even more DNA repair proteins, like ATM, would enhance its utility.